Cerebral blood flow in children and adolescents several years after concussion. (28th January 2019) - Brooks, Brian L.; Low, Trevor A.; Plourde, Vickie; Virani, Shane; Jadavji, Zeanna; MacMaster, Frank P.; Barlow, Karen M.; Lebel, R. Marc; Yeates, Keith Owen
ABSTRACT: Objectives : The long-term effects of concussion in youth remain poorly understood. The objective of this study was to determine the association between history of concussion and cerebral blood flow (CBF) in youth. Methods : A total of 53 children and adolescents with a history of concussion ( n  = 37) or orthopaedic injury (OI; n  = 16) were considered. Measures included pseudo-continuous arterial spin labelling magnetic resonance imaging to quantify CBF, post-concussion symptoms, psychological symptoms, and cognitive testing. Results : Participants (mean age: 14.4 years, 95% CI = 13.8–15.4, range = 8–19) were on average 2.7 years (95% CI = 2.2–3.1) post-injury. Youth with a history of concussion had higher parent-reported physical, cognitive, anxiety, and depression symptoms than children with OI, but the groups did not differ on self-reported symptoms (post-concussive or psychological) or cognitive testing. Global CBF did not differ between groups. Regional CBF analyses suggested that youth with a history of concussion had hypoperfusion in posterior and inferior regions and hyperperfusion in anterior/frontal/temporal regions as compared to those with OI. However, neither global nor regional CBF were significantly associated with demographics, pre-injury functioning, number of concussions, time since injury, post-concussive symptoms, psychological symptoms, or cognitive abilities. Conclusions : Youth with a history of concussion demonstrate differences in regional CBF (not global CBF), but without clear clinical expression.